Effects of MRS-Sago starch concentration on direct lactic acid production with controlled pH by Enterococcus faecium No. 78 - Liew, Nyuk Hsia (Universiti Malaysia Sarawak, UNIMAS, 2007)
The lactic acid production from starch can be made much more economical by using Enterococcus faecium No.78 to directly produce lactic acid from sago starch. The effects of different MRS-sago starch concentrations on direct lactic acid production were investigated in this study. The sago starch of 20 g/L, 30 g/L and 40 g/L were used as substrate in this study, with 0 g/L was used as control. Fermentation was conducted at 30°C, pH6.5 and agitation rate of 500rpm which were controlled constantly throughout fermentation. The increase in sago starch concentration had negative effect on the microbial growth. The highest microbial growth, 9.3 (log10 viable cells/mL) was achieved in fermentation by using 20 g/L sago starch. The maximum consumption of sago starch, 87.3% was observed in fermentation by using 20 g/L sago starch. The glucose consumption in all three fermentation trials were not different significantly. The highest lactic acid production, 22.9 g/L was achieved in fermentation by using 40 g/L sago starch. This shows that the lactic acid production increased in accordance with the utilization of higher sago starch concentration. The fermentation efficiency decreased slightly despite the usage of higher sago starch concentrations. Therefore, the optimum sago starch concentration for the highest lactic acid production was 40 g/L in consideration of the highest lactic acid production (22.9 g/L) while consuming the same amount of electricity, time and labour as in fermentation by using 20 g/L and 30 g/L sago starch.